Happiness and Moral Courage Among Iranian Nurses During the COVID-19 Pandemic: The Role of Workplace Social Capital - Pirdelkhosh, Maryam; Mohsenipouya, Hossein; Mousavinasab, Nouraddin; Sangani, Alireza; Mamun, Mohammed A. (Frontiers in Psychiatry, 2022)
Background: Accumulated resources and energy obtained via interpersonal relationships is called social capital, which can reduce the negative effects of pressure and stress related to the workplace by impacting happiness and moral courage. The present study for the first explored the effect of workplace social capital on moral courage and happiness in nurses during the COVID-19 outbreak. Methods: In this cross-sectional study, using a random sampling method, 169 nurses from three hospitals of East Mazandaran province, Iran, participated who worked in COVID-19 wards. The Onyx and Bullen Social Capital Questionnaire, the Sekerka’s Moral Courage Scale, and the Oxford Happiness Inventory were used in this study. Descriptive analysis, Pearson correlation analyses, and stepwise multiple regression were performed for data analysis. Results: The mean age of nurses was 31.38 ± 6.82 years. Workplace social capital was positively correlated with moral courage (r=0.29, p<0.01) and happiness (r=0.32, p<0.01). In addition, social capital was found to play a role in predicting moral courage and happiness [(R=0.261, p<0.001) and (R=0.294, p<0.001), respectively]. Conclusions: Workplace social capital is a vital organizational phenomenon affecting nurses' moral courage and happiness, especially during the COVID-19 pandemic. Thus, hospitals should be aware of the importance of social capital; they should ensure that all the practices and policies to be in place to develop and increase it.